Kinetics and thermodynamics of hexavalent chromium adsorption on to activated carbon derived from acrylonitrile-divinylbenzene copolymer - Duranoglu, Dilek; Trochimczuk, Andrzej W.; Beker, Ulker (ELSEVIER SCIENCE SA, 2012)
Adsorption of hexavalent chromium onto activated carbon derived from acrylonitrile-divinylbenzene has been studied in aspect to thermodynamic and kinetics. Chromium adsorption has been investigated using different process parameters like pH. carbon dosage, contact time and temperature. Maximum chromium adsorption capacity was obtained at low pHs and high temperature. Freundlich isotherm model represented the experimental data very well. Chromium adsorption followed the pseudo-second-order kinetic model, which indicated chemical adsorption. The activation energy of adsorption was calculated as 26.07 kJ/mol. The mean free sorption energy was >22 kJ/mol and adsorption enthalpy was +73.77 kJ/mol. All thermodynamic and kinetic calculations indicated the chemical interaction between the carbon surface and chromium ions. The isosteric heat of adsorption increased with surface loading. indicating energetically homogeneous surface of produced activated carbon. Adsorption mechanism has been investigated using X-ray photoelectron spectroscopy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Activated carbon; Chromium; Adsorption; Kinetics; Thermodynamics; X-ray photoelectron spectroscopy (XPS); AQUEOUS-SOLUTION; CR(VI) ADSORPTION; REMOVAL; BIOSORPTION; BATCH; ZINC; OPTIMIZATION; ADSORBENTS; SORPTION; SAWDUST; Engineering